Enantioselective Construction of All-Carbon Quaternary Centers by Branch-Selective Pd-Catalyzed Allyl-Allyl Cross Coupling - Zhang, Ping (2011)
The Pd-catalyzed cross coupling of racemic tertiary allylic carbonates and allyl boronates is described. This reaction generates all-carbon quaternary centers in a highly regioselective and enantioselective fashion. The outcome of these reactions is consistent with a process that proceeds by way of 3,3’-reductive elimination of bis(η(1)-allyl)palladium intermediates. Strategies for distinguishing the product alkenes and application to the synthesis of cuparenone are also described.